Looping cycles for low carbon technologies: A survey of recent research activities in Naples. (15th May 2020) - Coppola, A.; Senneca, O.; Scala, F.; Montagnaro, F.; Salatino, P.
Abstract: In the last decades several looping processes for clean utilization of fossil resources have been proposed with the aim of providing transient/long-term solutions to the challenge of near-zero emission energy production. A selection of solids looping processes for both carbon oxidation/gasification and CO2 capture/utilization will be surveyed, with a specific focus on the contribution given by the research group active in Naples. A novel concept has been developed (CarboLoop) to accomplish capture-ready combustion/gasification of carbon through iterated oxidation/desorption cycles. The idea is that alternated oxygen chemisorption on carbon followed by thermal desorption of oxides as CO/CO2 provide a path with inherent oxygen separation and concentrated CO/CO2 streams. The path to exploitation of the CarboLoop is laid by elucidation of the thermochemistry of carbon oxidation throughout dynamic oxidizing/reducing cycles. Calcium Looping (CaL) provides a feasible path to accomplish carbon capture from CO2 -bearing exhaust. Its efficiency is affected by sorbent thermal sintering and by particle attrition/fragmentation. There is still a lack of characterization of the concurrent effect of steam and SO2 in terms of sorbent availability and selective uptake of CO2 . The performance of Ca-based sorbents has been scrutinized in the frame of ternary CO2 -SO2 -H2 O environments. Methanation is an attractive path to CO2 utilization. Sorption-Enhanced Methanation (SEM) exploits the favourable effect on thermodynamics of continuous in-situ removal of steam generated by methanation by a sorbent. SEM is conveniently performed as a looping process, whose performance has been characterized by means of a novel test rig configuration based on two-interconnected fluidized beds.